A comparative study on treatment of two and three walled periodontal bony defects utilizing open flap debridement with and without enamel matrix derivatives - Soleimani Shayesteh Y.; Mohseni Salehi Monfared SH; Eskandarion S. (Tehran University of Medical Sciences, 2006)
Background and Aim: Intrabony periodontal defects are important problems in periodontology and up to now several ways have been suggested for their treatment .Treatment with enamel matrix derivatives (EMD) has been shown to enhance periodontal regeneration. There is limited information available from clinical trials regarding the performance of EMD in the treatment of periodontal intrabony defects. This study was designed to compare the clinical and radiographic effects of EMD treatment to that of open flap debridment (OFD) for two and three walled intrabony defects. Materials and Methods: 18 patients were included in this clinical trial which have 24 two and/ or three intrabony defects. Defects were randomly divided into two groups (test and control). Defects in test group were treated with flap surgery plus EMD and in control group with open flap debridment. At baseline and at 3 and 6 months follow up, clinical and radiographic measurements were performed. Data were analyzed using Greenhouse-Geisser test with p<0.05 as the limit of significance. Results: At 3 and 6 months, mean probing pocket depth reduction was greater in the test group (EMD) (4.33 mm and 4.70 mm) compared to the OFD group (2.54 mm and 3.09 mm). Mean values for clinical attachment gain in the EMD group after 3 and 6 months were 4.29 mm and 4.98 mm, and in OFD group were 2.83 and 2.82 mm respectively. Radiographic bone gain measured by radiovisiography technique was greater in the EMD group compared to the OFD group (4.66 mm in EMD and 1.11 mm in OFD group after 3 months and 5.78 mm in EMD and 1.39 mm in OFD group after 6 months). Conclusion: Based on the results of this study, treatment with flap surgery and EMD compared to open flap debridment, produced more favorable clinical improvements in two and three walled intrabony defects.